Frammenti liturgico-musicali sciolti alla Biblioteca nazionale centrale di Roma - Corbo, Alessandra; Tangari, Nicola (Scrineum, 2020)
The Biblioteca nazionale centrale of Rome preserves a collection of parchment fragments from medieval manuscripts containing liturgical music. These fragments were found in the bindings of manuscript or printed books and separated from the volumes where they had been reused; they are now part of some special series of the Library. The collection is very interesting as it witnesses different musical notation and, in some cases, rare liturgical chant. Furthermore, it shows the different origins of the fragments, from Italy and Northern Europe. This article includes a methodological introduction with an overview of past researches on manuscript fragments and their description, some comments on the most interesting features concerning liturgy and music and a final catalogue of all the fragments. The latter provides a detailed description of each folio, including codicological and paleographical informations and a detailed list of all the pieces, with references to common editions and repertoires, and a final index of the incipits.